Therapeutic effect of natural herbs in dentistry: a narrative review - Mat Hussin, Nur Farhana; Altarawneh, Hazem Mofreh Dakhilallah; Wan Nik, Wan Noor Nazayan; Arzmi, Mohd Hafiz; Ismail, Azlini; Ab Ghani, Siti Mariam (Universiti Malaya, 2024)
Objectives: Natural herbs have increased attention due to their therapeutic and general health-improving qualities as reported in the literature. This review paper aims to explore the therapeutic effects of natural herbs in dentistry and to describe the various herbal sources, active compounds and its dental applications. Methodology: A literature search was conducted using WoS, Pubmed, and Scopus with the search terms ‘herbal’ AND ‘dentistry’ AND ‘alternative treatment’. Articles related to natural herbs and dental applications from the past 15 years until September 2023 were gathered. The inclusion criteria for this study were in-vitro experiments and clinical studies. Result: 512 articles were extracted from the search with 128 falling under the inclusion criteria (86 in-vitro experiments and 42 clinical studies). It was observed that 15 therapeutic properties were extensively examined, with antimicrobial studies being the most prevalent (50.0%), while the least explored properties were pulp-capping and obturation material (0.8%). Diseases such as denture stomatitis, oral candidiasis, and gingivitis were highly reported to have benefited from natural herbal medicine as an alternative treatment option. Herbals such as propolis, green tea, ginger, Zataria multiflora, chitosan, garlic, Artemisia, Schinus terebinthifolius Raddi, Uncaria tomentosa, Punica granatum, and Ricinus communis were found to be useful in the treatment of denture stomatitis. Rhizoma imperatae extract has been added to oral care products and has shown an excellent effect on reducing gingivitis. Pistacia atlantica extract mouthwash was reported to be effective against dental plaque bacteria and subgingival microorganisms. Conclusion: Numerous natural herbs have been extensively documented to have therapeutic effects in certain dental diseases as supported by laboratory and clinical studies. However, comprehensive guides such as the clinical indications, therapeutic doses and application methods were with minimal evidence that can be derived from the literature. More extensive clinical trials are to be conducted on the therapeutic efficacy of natural herbs in dentistry.